Developing a Local Wisdom-Based Digital Resource for English for Tourism in Vocational High Schools in Banjarmasin - Fadilla, Raisa; Arief, Yusuf Al (Universitas Muhammadiyah Kalimantan Timur, 2024)
Tourism graduates from various SMKs in South Kalimantan are expected to be able to become initiators of tourism development both at the regional and national levels and be able to become a driving force for tourism actors in building economic competitiveness through the tourism sector. English as an international language is needed by the community, especially for Indonesian tourism. As one of the required subjects taught in vocational high schools, the problems arises in teaching English because there are no attractive and interesting learning resources for teachers and students about teaching English specifically for tourism majors in vocational high schools in Banjarmasin. Teachers in some schools in Banjarmasin, especially in wetland areas, have limited access to information on teaching English for Tourism. In relation to the university policy and seeing the importance of achieving teaching and learning objectives as well as the lack of suitable digital learning resources for teaching English for tourism students, especially those located in wetland areas, this research aimed to produce digital learning resources in the form of a website which is based on local wisdom for vocational high school students. This research applied a Research and Development design because it aimed to develop a product by paying attention to the needs analysis. It is expected that the results of this research can not only improve students' academic performance but also facilitate teachers to conduct effective and meaningful teaching in wetland areas.